Improvement in influenza vaccination rates in a pediatric sickle cell disease clinic. Issue 4 (24th December 2014) - Sobota, Amy E.; Kavanagh, Patricia L.; Adams, William G.; McClure, Elizabeth; Farrell, Delmaude; Sprinz, Philippa G.
<x xml:space="preserve">Abstract</x> Background Children with sickle cell disease (SCD) are at increased risk of complications from influenza. However, despite widespread recommendations that these patients receive an annual influenza immunization, reported vaccination rates remain very low at under 50%. Procedure Our aim was to increase the influenza vaccination rate among our pediatric patients with SCD aged 6 months to 21 years over two influenza seasons, 2012–2013 and 2013–2014, to 80%, consistent with the Health People 2020 goal. We used multiple quality improvement methods, based on the literature and our previous experience in other aspects of SCD care, including parent and provider education, enhancement of our EHR, use of a SCD patient registry and reminder and recall done by a patient navigator. Results We vaccinated 80% of our pediatric patients with SCD for influenza during the 2012–2013 season and 90% of patients in 2013–2014. Our early season vaccination rates were nearly double that of those for the general population. Conclusions Use of quality improvement methods can increase rates of influenza vaccination for this high‐risk population, suggesting that less health care utilization and lower cost might result. Pediatr Blood Cancer 2015;62:654–657. © 2014 Wiley Periodicals, Inc.